Contributions on the energy flow modeling in a self-sustainable wireless energy transfer system based on efficient inductive links - Fajardo Jaimes, Arturo (2018)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Elétrica, Florianópolis, 2018.